Analysis of Content, Source and Impact of Heavy Metals in Sombori Island, Central Sulawesi, Indonesia - Hasria, Hasria; Usman, Ida; Saeri, Karim; Nasaruddin; Sara Septiana; Rais, Mohammad; Harisma, Harisma; Musrajab, Silo (UIR PRESS, 2026)
A study was conducted on Sombori Island, Central Sulawesi. The purpose of this study was to determine the content of heavy metals and the origin of contamination and the impact of heavy metal contamination. Seawater samples totaling 30 stations were analyzed in the form of total suspended solids (TSS), pH, salinity and heavy metal content of hexavalent chromium (Cr6+) and nickel (Ni) using Atomic Absorption Spectrometry (AAS) analysis. The heavy metals chromium (Cr) and nickel in the sediment were analyzed using flame Atomic Absorption Spectrometry (AAS). The results of the study showed that heavy metals in seawater in the form of Ni are still safe for the marine ecosystem of the research area. However, the heavy metal Cr6+ has contaminated several marine waters stations because it has exceeded the established quality standards so that it can have a negative impact on the marine ecosystem including humans through the food chain. The content of heavy metal Cr in marine sediments has not passed the established sediment quality standards. However, for heavy metal Ni in sediment, it has exceeded the established sediment quality standards so that it has had a negative impact on the marine ecosystem that lives and feeds around/on the sediment including humans through the food chain. Sources of contamination of heavy metals in water and sediment are from the weathering of ultramafic rocks containing heavy metals, mining activities, shipping activities using fossil fuels, the use of ship paint containing heavy metals, solid waste from ships containing heavy metals and domestic waste.